Dietary Patterns in the Argentinian Population and Their Association With Sociodemographic Characteristics: Results From the ELANS Study (2014–2015) - Mendez, Ignacio; Fasano, Maria Victoria; Guajardo, Viviana; Zonis, Luciana; Kovalskys, Irina (Frontiers in Nutrition, 2022)
Aim: To describe dietary patterns in the Argentinian population and their association with sociodemographic characteristics. Methods: Cross-sectional analysis of Argentina's food consumption and sociodemographic data of 1266 men and women between 15 and 65 years from the Latin American Study of Nutrition and Health carried out between March 2014 and December 2015. Dietary patterns were identified using factor analysis and median factor scores were calculated for gender, age, region, BMI, socioeconomic, education, and physical activity categories. Results: Five dietary patterns were identified. Western, Local Western, and Rural were generally characterized by high consumptions of animal fats, sugar-sweetened beverages, meats or processed meats, pizza and empanadas, sweets, pastries, and low consumption of fruits and vegetables. Traditional pattern was mainly characterized by consumption of oils, starchy vegetables, and red meat; and Sweet Prudent by milk and yogurt, vegetables, fruit, artificially sweetened beverages, sweets, and cookies. Higher adherence to the Sweet Prudent pattern was observed in women, in people who meet physical activity guidelines and higher socioeconomic and educational levels. Higher adherence to Traditional pattern was only observed for men. Higher adherence to the rest of the patterns was observed mostly by men, young, leaner, lower socioeconomic and educational levels, not meeting physical activity guidelines, from the metropolitan area of Buenos Aires or northern regions. Conclusions: Food consumption in Argentina is expressed in a diversity of dietary patterns. Men, younger, sedentary individuals, with lower socioeconomic and educational level, from the metropolitan area of Buenos Aires and northern regions; seems to have higher adherence to least healthy dietary patterns.